An interleukin-1 polymorphism additionally intensified by atopy as prognostic factor for aseptic non-mechanical complications in metal knee and hip arthroplasty - Summer, B.; Lill, D.; Remmel, K.; Schraml, A.; Schopf, C.; Banke, I. J.; Kuechenhoff, H.; Maierhofer, T.; Endres, S.; Thomas, P. (Frontiers in Immunology, 2022)
Background In contrast to infection or mechanical issues joint replacement failure following inflammatory adverse reactions is poorly understood. Objective To assess the association of IL-1β polymorphisms and history of allergy with aseptic non-mechanical complications following arthroplasty. Methods In 102 patients with aseptic non-mechanically caused symptomatic knee or hip arthroplasty (SA) and 93 patients with asymptomatic arthroplasty (AA) questionnaire-based history, patch test with at least standard series, lymphocyte transformation test (LTT) with nickel, cobalt and chromium and interleukin-1 polymorphism analysis were done. Three polymorphisms of the IL1B gene [IL-1b -3954 (rs1143634), IL-1b -511 (rs16944) and IL-1b -31 (rs1143627)] and one polymorphism of the IL1RN gene [IL1RN intron 2, variable number of tandem repeats, VNTR (rs2234663)] were assessed by PCR and gel electrophoresis. Results We found no significant difference in smoking history and atopy but 25% versus 10% of self-reported metal allergy in SA versus AA; the patch test (respective, LTT) for metal sensitivity was more often positive in SA patients. The allele 498 bp of the IL1RN polymorphism occurred significantly more often in the SA group (37% versus 11%; p < 0.0001). Upon additional presence of atopy, the difference was even greater (60% vs 10%) (p < 0.000001). There was no association of IL-1 polymorphisms with metal allergy. Conclusion The IL1RN VNTR allele 498 bp was strongly associated with SA. In patients with a history of atopy, presence of the IL1RN VNTR allele 498 bp led to a four-fold higher SA prevalence compared to patients without this allele.